Evaluation of Tourist Satisfaction Levels in Mangrove Ecotourism Using the Net Promoter Score (NPS) Method - Latuni, Fandy Yones; Mandey, Silvya Lefina; Soegoto , Agus Supandi; Kawet, Raymond Christian; Rondonuwu, Christy Natalia; Paat, Franda Benedicta; Datualo, Diane Natalin; Lumi, Isye (Sam Ratulangi University, 2025)
This study aims to assess the level of tourist satisfaction with the Darunu Mangrove Ecotourism Village using the Net Promoter Score (NPS) method. This approach was chosen because it is effective in measuring not only tourist satisfaction but also loyalty behavior, which is reflected in tourists' willingness to recommend the destination to others. This study used a quantitative descriptive method involving 100 tourists selected by accidental sampling. Data were obtained through field observations, brief interviews, and a questionnaire using a Likert scale. The findings show that overall tourist satisfaction is in the “good” category, with an average NPS score of 52.7. The highest-ranking indicators are friendly environmental conditions (72), intention to revisit (69), affordability (68), and destination attractiveness (66). Conversely, the facilities (40) and accessibility (48) indicators have the lowest scores, indicating the need for improvements in infrastructure and visitor comfort. The results demonstrate that community involvement and sustainable environmental management play a crucial role in shaping positive tourism experiences. Furthermore, this study provides strategic insights for destination managers and local governments to enhance the development of sustainable mangrove-based ecotourism in the coastal areas of North Minahasa. Keywords: tourist satisfaction, mangrove ecotourism, tourist loyalty, Net Promoter Score (NPS), destination management, sustainable tourism